Alternatives to Traditional Physical Science Laboratory Experiences: A Review - Mercy Ogunsola-bandele; Dietmar Kennepohl (West African Journal of Open and Flexible Learning)
There is a lot of concern around the increasing difficulties faced in providing hands-on experiences for the science learner who is separated from the institution in space and time. This is evidenced by conflicting research reports on students’ ability to manipulate laboratory equipment after participating in online experimentation. Since the importance of the laboratory practical cannot be ignored in distance delivery, there is a need to explore alternatives to the on-campus laboratory. The current research conducted a review of peer-reviewed empirical articles on these alternatives which include home kit labs, virtual labs, and remote labs. It included 70 selected articles published in English from 2006 to 2022. Although the review revealed a preference for the virtual and remote lab over the traditional one, the advantages of the latter cannot be ignored. A summary list of advantages (e.g., increased flexibility and access) and disadvantages (e.g., no face-to-face contact and some additional costs) outlined in the articles is presented.